The Impact of Covid-19 on The Halal Tourism - Aam Slamet Rusydiana; Aisyah As-Salafiyah; Lina Marlina (Islamic Marketing Review, 2022)
This study aims to determine the map of the development of research on the theme of halal tourism during the COVID-19 pandemic published by digital object identifier-equipped journals. The study was conducted in November 2020. The data analyzed were more than 50 published papers. The object of study is a published journal published in 2020. The data is then processed and analyzed using the VOSviewer application program to determine the bibliometric mapping of the development of halal tourism research. The results showed that the most popular countries used as the object of study were Indonesia with 18 papers and Malaysia with 13 papers. The research development map of this theme is divided into 4 clusters. Cluster 1 consists of 11 topics, cluster 2 consists of 11 topics, cluster 3 consists of 10 topics and cluster 4 consists of 8 topics. The findings from this study indicate that the halal tourism sector is also affected by COVID-19 and various countries have made efforts to minimize this impact. The adverse effects of COVID-19 have quite an impact on the halal tourism sector today and in the future, this is because visitors and tourists are reluctant to travel because they are worried about health risks despite the COVID-19 pandemic has ended. However, players in the halal tourism sector must continue to make improvements, by continuing to improve the facilities provided to support health insurance.